2019
DOI: 10.4274/ejgg.galenos.2019.32
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Case of Psoas Abscess in an Elderly Patient

Abstract: Psoas abscess (PA), the accumulation of suppurative fluid in the fascia surrounding the psoas muscle, is a rare condition, with difficult diagnosis. Pain, fever, and limping are its main symptoms. In this paper, we report a case of PA presenting with non-specific symptoms, such as pain and fatigue. After the diagnosis, drainage of PA was performed, and intravenous antibiotic treatment was started immediately. The patient was discharged with improvements in his general condition after three weeks of treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It can occur due to contiguous spread from adjacent structures or hematogenous spread from a distant site. The incidence is low, but the use of computed tomography has increased the frequency of this diagnosis, with most cases diagnosed postmortem 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can occur due to contiguous spread from adjacent structures or hematogenous spread from a distant site. The incidence is low, but the use of computed tomography has increased the frequency of this diagnosis, with most cases diagnosed postmortem 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Primary IPA results from an organism's hematogenous or lymphatic spread from a distant site. Risk factors include diabetes, intravenous drug use, human immunodeficiency virus (HIV) infection, renal failure, and other forms of immunosuppression [1,2]. Secondary IPA occurs when a nearby infectious/inflammatory process extends directly into the iliopsoas [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoas Abscess (PA) is uid accumulation in fascia around the psoas muscles which plays a vital role in the exion of trunk [1]. According to a study, the mean time span between the onset of symptoms and PA diagnosis was found to be 22 days with one third of patients diagnosed after 42 days [2].…”
Section: Introductionmentioning
confidence: 99%